1979
DOI: 10.1007/bf00496070
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cannabidiol, alone and in combination with ethanol, on human performance

Abstract: Fifteen volunteers received cannabidiol (CBD) (320 microgram/kg) or placebo (both orally, T0), and 60 min later they consumed an ethanolic beverage (0.54 g/kg) or placebo. The effects were measured at T1 (100 min after CBD ingestion), T2 (160 min) and T3 (220 min) using cognitive, perceptual and motor function tests. Factorial analysis indicated that test procedures could be adequately expressed by three rotated factors: A reaction speed factor (I), a standing steadiness factor (II) and a psychomotor coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
2
33
1
2
Order By: Relevance
“…Our results are consistent with previous experimental and epidemiological studies that have reported additive effects of alcohol and marijuana on driving performance and crash risk (Dubois et al 2015; Bates & Blakely 1999; Sewell et al 2009; Doty et al 1992; Belgrave et al 1979; Drummer et al 2004; Chesher 1986) and possibly synergistic (Brault et al 2004; Biecheler et al 2008; Sutton 1983; Perez-Reyes et al 1988) effects. For instance, a recent case–control study found that, relative to drivers using neither alcohol nor marijuana, drivers who tested positive for both alcohol (BAC ≤ 0.08 g/dL) and marijuana had up to 128% increased odds of committing an unsafe driver action compared to 16% for those using marijuana alone and 117% for those using alcohol (BAC ≤ 0.08 g/dL) alone (Dubois et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous experimental and epidemiological studies that have reported additive effects of alcohol and marijuana on driving performance and crash risk (Dubois et al 2015; Bates & Blakely 1999; Sewell et al 2009; Doty et al 1992; Belgrave et al 1979; Drummer et al 2004; Chesher 1986) and possibly synergistic (Brault et al 2004; Biecheler et al 2008; Sutton 1983; Perez-Reyes et al 1988) effects. For instance, a recent case–control study found that, relative to drivers using neither alcohol nor marijuana, drivers who tested positive for both alcohol (BAC ≤ 0.08 g/dL) and marijuana had up to 128% increased odds of committing an unsafe driver action compared to 16% for those using marijuana alone and 117% for those using alcohol (BAC ≤ 0.08 g/dL) alone (Dubois et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, relatively little is known about the neurocognitive consequences of simultaneous use, and previous findings in adults have been conflicting. Some have found no additive acute motor or cognitive effects of combined cannabidiol (CBD) or THC and alcohol use (Belgrave et al, 1979b;Liguori et al, 2002), while others have found cumulative acute effects of THC or CBD and alcohol in perceptual and motor function (Belgrave et al, 1979a;Chait & Perry, 1993;Consroe et al, 1979). Additionally, simultaneous use of CBD and ethanol actually decreased blood alcohol levels (Consroe et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Although the CB 2 cannabinoid receptor partially mediates the antiinflammatory effects of THC (3), CBD does not bind well to the known cannabinoid receptors (4); this low affinity results in the inability of CBD to produce the subjective ''high'' and cognitive effects that are characteristic of marijuana and THC (5,6). To date, the mechanism by which CBD decreases inflammation is unknown, although micromolar concentrations of CBD have been shown to inhibit lipoxygenase activity (7).…”
mentioning
confidence: 99%